Claiming knowledge : strategies of epistemology from theosophy to the New Age - Hammer, Olav (Studies in the history of religions, 2004)
This work deals with the transformation of religious creativity in the late modern West. Its point of departure is a set of esoteric beliefs, from Theosophy to the New Age. It shows how these traditions have adapted to the cultural givens of each successive epoch.